KESEJAHTERAAN LANSIA DAN BEBERAPA FAKTOR YANG MEMPENGARUHI DI DESA DANGIN PURI KAUH - Raka Riani Tanaya; I Gusti Wayan Murjana Yasa (Puslit Kependudukan dan Pengembangan SDM Universitas Udayana, 2015)
Indicators of success of development is the increasing life expectancy of the population. The purpose of this studywas to determine the effect of religiosity , economic conditions , and access to health simultaneously and partiallyto the welfare of the elderly in Dangin Puri Kauh . Then the sample was taken 86 of the total 624 elderly seniorswho are in Dangin Puri Kauh . This study used quantitative analysis techniques namely multiple linear regressionanalysis . Based on the results of the study , obtained information that Religiosity ( X1 ) , Economics ( X2 ) , andHealth ( X3 ) , has a significant effect simultaneously and partially on the elderly Welfare ( Y ) on Dangin Puri Kauh. This means that the higher the religiosity ( X1 ) , Economics ( X2 ) , and Health ( X3 ) owned by the elderly , theelderly Welfare Kauh Dangin Puri Denpasar will increase .